Superstring vertex operators in an AdS(5) x S-5 background - Berkovits, N.; Chandia, O. (Elsevier B.V., 2001)
A quantizable action has recently been proposed for the superstring in an AdS(5) x S-5 background with Ramond-Ramond flux. In this paper we construct physical vertex operators corresponding to on-shell fluctuations around the AdS(5) x S-5 background. The structure of these AdS(5) x S-5 vertex operators closely resembles the structure of the massless vertex operators in a flat background. (C) 2001 Elsevier B.V. B.V. All rights reserved.